Diseño de una crema tópica antibiótica a partir de extracto de Polygonum punctatum (2020)
Antibiotics have been since long ago, one of the most used medical advances to treat infectious diseases. This kind of diseases include dermal infections such as impetigo, skin abscesses, cellulitis, surgical wound infection, botryomycosis, epidural abscesses, scalded skin syndrome and so on. All of them are the result of a local infection of different strains of Staphylococcus Aureus, a quite common gram positive bacteria. Thus, multiple alternatives have been developed to treat such dermal infections, where some topical antibiotics stand out because of their active pharmaceutical ingredients(API), derived from microorganisms. However, some of this products have shown secondary effects on the patients. Therefore, this project presents the design of a topical cream whose API is the extract of the leaves of Polygonum punctatum, which is a very common medicinal plant from the wetlands of the American continent, and it's traditionally used as a treatment for infectious diseases. Based on the study of the state of art, expected properties, base formulation and lab scale productive process where stablished for the product. This allowed the creation of a starting point for the investigation on the product design for this alternative, showing that it's feasible and has a wide area for future work.--Taken from the Degree Document Format.